Social Determinants of Immigrant Women's Mental Health - Mahin Delara (Hindawi Limited, 2016)
Migration is a population movement with enormous challenges for immigrant women that influence their mental health. Mental health is a social issue and its determinants need to be recognized for health policy making. This paper reviews and consolidates findings from the existing literature on social determinants of immigrant women's mental health within a socioecological framework. Findings of this review revealed that mental health of immigrant women is an outcome of several interacting determinants at social, cultural, and health care system levels and hence calls for many different ways to promote it. Recommendations for mental health promotion of immigrant women with respect to research, education, practice, and policy are explored.